Effects of the Chinese herbal formula San-Huang Gu-Ben Zhi-Ke treatment on stable chronic obstructive pulmonary disease: a randomized, double-blind, placebo-controlled trial - Lyu, Tianyi; Li, Demin; Lei, Xiang; Zhang, Yuteng; Cheng, Shilei; Shu, Xinyang; Zhang, Hongchun (Frontiers in Pharmacology, 2023)
The aim of this study was to evaluate the efficacy and safety of the Chinese herbal formula San-Huang Gu-Ben Zhi-Ke (SHGBZK) as a treatment for patients with stable chronic obstructive pulmonary disease (COPD) diagnosed with lung-spleen Qi deficiency. Method: A randomized, double-blind, placebo-controlled trial was designed. 98 adults aged between 40 and 80 years with stable COPD diagnosed with lung-spleen Qi deficiency were included. All participants received basic treatment for COPD. Patients in the experimental group took SHGBZK, while the control group took placebo. The primary outcome was the frequency of acute exacerbation. The secondary outcomes were lung function, symptom score, exercise capacity and quality of life. Results Of 98 patients who underwent randomization, 50 patients in the SHGBZK group and 48 in the placebo group were included in the full analysis set. After 24-week therapy and 28-week follow-up, patients in treatment group had significant improvements in symptom, exercise capacity and quality of life. After Subgroup analysis, the frequency of acute exacerbation in patients with a COPD Assessment Test (CAT) score of at least 10 or a modified Medical Research Council (mMRC) score of at least 2 was significantly lower in the SHGBZK group than in the placebo group. Lung function in patients with frequent exacerbation was significantly higher in the SHGBZK group than in the placebo group. The incidence of adverse events was generally similar in the two groups. Conclusion SHGBZK had beneficial effects on symptom, exercise capacity and quality of life in stable COPD patients. SHGBZK also had the potential to reduce the frequency of exacerbation and improve lung function in specific groups of COPD patients.